Time dependent viscoelastic rheological response of pure, modified and synthetic bituminous binders - Airey, G. D. (Springer, 2016)
Bitumen is a viscoelastic material that exhibits both elastic and viscous components of response and displays both a temperature and time dependent relationship between applied stresses and resultant strains. In addition, as bitumen is responsible for the viscoelastic behaviour of all bituminous materials, it plays a dominant role in defining many of the aspects of asphalt road performance, such as strength and stiffness, permanent deformation and cracking. Although conventional bituminous materials perform satisfactorily in most highway pavement applications, there are situations that require the modification of the binder to enhance the properties of existing asphalt material. The best known form of modification is by means of polymer modification, traditionally used to improve the temperature and time susceptibility of bitumen. Tyre rubber modification is another form using recycled crumb tyre rubber to alter the properties of conventional bitumen. In addition, alternative binders (synthetic polymeric binders as well as renewable, environmental-friendly bio-binders) have entered the bitumen market over the last few years due to concerns over the continued availability of bitumen from current crudes and refinery processes. This paper provides a detailed rheological assessment, under both temperature and time regimes, of a range of conventional, modified and alternative binders in terms of the materials dynamic (oscillatory) viscoelastic response. The rheological results show the improved viscoelastic properties of polymer and rubber modified binders in terms of increased complex shear modulus and elastic response, particularly at high temperatures and low frequencies. The synthetic binders were found to demonstrate complex rheological behaviour relative to that seen for conventional bituminous binders.